Rethinking Lasem: Some Notes and Challenges on Heritage Conservation - Martokusumo, Widjaja; Astuti, Erika Yuni; Suryaningsih, Febriyanti; Purwestri, Nadia; Malagina, Agni (RUAS, 2024)
The discussion on cultural heritage has evolved to integrate both tangible and intangible aspects in urban heritage management. Heritage conservation now faces challenges related to resources and the condition of urban elements. When assessing cultural significance, it's important to look beyond physical objects and consider social and cultural factors. The Lasem revitalization project has focused on improving public spaces and street corridors, but the protection of historical urban features is often overlooked, causing new problems. This research used surveys, interviews, and participation mapping to gather data. The analysis framework is based on understanding historical urban features, cultural significance, and people-centered conservation. The study emphasizes the need for a holistic approach to both tangible and intangible heritage in Lasem’s historic areas and finds that people-centered conservation views heritage as a socio-cultural construct.